Analysis of distributed consensus protocols with multi-equilibria under time-delays - CİHAN, ONUR (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this paper, we propose a novel method for addressing the multi-equilibria consensus problem for a network of n agents with dynamics evolving in discrete-time. In this method, we introduce, for the first time in the literature, two concepts called primary and secondary layer subgraphs. Then, we present our main results on directed graphs such that multiple consensus equilibria states are achieved, thereby extending the existing single-state consensus convergence results in the literature. Furthermore, we propose an algorithm to determine the number of equilibria for any given directed graph automatically by a computer program. We also analyze the convergence properties of multi-equilibria consensus in directed networks with time-delays under the assumption that all delays are bounded. We show that introducing communication time-delays does not affect the number of equilibria of the given network. Finally, we verify our theoretical results via numerical examples. (C) 2017 The Franklin Institute. Published by Elsevier Ltd. All rights reserved.
Keywords: VARYING DELAYS; CLUSTER CONSENSUS; CONVERGENCE SPEED; AVERAGE CONSENSUS; SYSTEMS; NETWORKS; TOPOLOGIES; AGENTS; SYNCHRONIZATION; OPTIMIZATION